Frenectomy Using Z-Plasty Technique in Case of Aberrant Frenum on Aesthetic Zone - Wildan, Muhammad Nabeel; Herawati, Dahlia (Indonesian Dental Association, 2024)
Background: Aberrant frenum can cause many problems such as central diastema, food impaction, dental caries, and aesthetic problems. This case can be handled with frenectomy, which is Z-Plasty technique can be used to treat thick and wide frenulum associated with papillary penetrate and central diastema. Case Report: A 17 years old girl was referred from orthodontist to Department of Periodontics, RSGM UGM Prof. Soedomo Yogyakarta for treatment of maxillary labial frenulum. Intra-oral examination revealed a diastema on the maxillary central incisor of 2.5 mm and frenulum attachment extended to the palatine papilla. In this case, collaborative perio-ortho treatment was carried out, frenectomy with Z-Plasty technique done to correct thick frenulum and fixed orthodontic treatment to correct central diastema after completion of periodontal treatment. Evaluations are carried out every 7 days for the first 2 weeks then at 3 and 6 months after periodontal procedure. Conclusion: Frenectomy using Z-Plasty technique was able to correct wide and thick frenulum that extends to the palatine papilla. Good wound healing, minimal scarring and color matching the surrounding tissue, and perio-ortho collaboration treatment was successfully carried out with satisfactory results according to the patient's wishes.